2010
DOI: 10.1111/j.1468-3083.2009.03416.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity, trypsin inhibitory capacity and total antioxidant capacity in psoriasis

Abstract: Serum ADA activity and sTIC were increased in psoriatic patients. In parallel, serum total anti-oxidant activity was decreased in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
4
14
0
1
Order By: Relevance
“…These results are in agreement with recent studies that have shown a significant reduction of the total antioxidant capacity of plasma in patients with psoriasis in comparison with healthy controls 29 …”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with recent studies that have shown a significant reduction of the total antioxidant capacity of plasma in patients with psoriasis in comparison with healthy controls 29 …”
Section: Discussionsupporting
confidence: 93%
“…23 Accordingly, there is an imbalance in the oxidant-antioxidant system in psoriasis patients, and increased ROS levels might play a role in the pathogenesis of this disease. 21,22,24,25 Both Gabr and Al-Ghadir 21 and Hashemi et al 25 have reported low TAC values in psoriasis patients compared with control groups. A decrease in serum antioxidants accompanied by an increase in serum oxidant levels has been reported in psoriasis patients, as well.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies report high ADA in the sera of psoriatic patients than that of the healthy controls. 21,22 Tikhonov et al 9 , found double activities of ADA and purine nucleoside phosphorylase (PNP) in the skin of psoriatic patients. In accordance with our results Hashemi et al 21 and Yildirum et al 22 found no correlation between serum ADA and PASI score.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Tikhonov et al 9 , found double activities of ADA and purine nucleoside phosphorylase (PNP) in the skin of psoriatic patients. In accordance with our results Hashemi et al 21 and Yildirum et al 22 found no correlation between serum ADA and PASI score. Many studies have also reported a decrease of serum ADA levels after psoriasis treatment with different modalities including cyclosporine, etanercept, PUVA, and PTU.…”
Section: Discussionmentioning
confidence: 99%